A generalized Riemann- Stieltjes integral on time scales and discontinuous dynamical equations - Barbanti, Luciano [UNESP]; Damasceno, Berenice Camargo [UNESP]; Chavarette, Fábio Roberto [UNESP]; Balthazar, José Manoel [UNESP] (My University, 2011)
This paper is concerned with a generalization of the Riemann- Stieltjes integral on time scales for deal with some aspects of discontinuous dynamic equations in which Riemann-Stieltjes integral does not works. © 2011 Academic Publications.
Keywords: Discontinuous dynamic systems; Existence of solutions; Fredholm-Stieltjes integral equations; Riemann-Stieltjes integral; Time scales